Human resources in dentistry geographical distribution in Brazil and Colombia: Comparative analysis from the perspective of historical institutionalism (Research, Society and Development, 2024)
The Human Resource in Health constitutes one of the six core components of health systems, playing a crucial role in realizing the right to health and ensuring access and service quality. Additionally, institutional frameworks within each country, encompassing laws, decrees, political systems, and health system characteristics, exert a significant influence on HRH and, specifically, in Human Resources in Dentistry (HRD). Both Brazil and Colombia experienced neoliberal reforms in the 1990s, introducing new institutions within the existing model and altering the social, political, and economic dynamics of each country. This study aims to examine the impact of institutional arrangements stemming from the 1990s neoliberal reforms in Brazil and Colombia on HRDs, focusing on geographic distribution. Employing a comparative analysis and adopting a historical institutionalism perspective, the research relies on a methodology involving multiple case studies with embedded units. Results reveal that the neoliberal reforms represented critical junctures reshaping the social and economic policies of both nations. In this context, the reforms influenced wealth distribution in both countries, subsequently impacting the unequal geographical distribution of HRD. These effects were closely tied to factors such as labor flexibility and the unregulated, unplanned expansion of dentistry courses. These elements initiated positive feedback loops, characterized by path dependence and increasing returns, which have contributed to the institutionalization and persistence of these phenomena within the state and have become entrenched in HRDs over time.